Disorders of histone methylation: Molecular basis and clinical syndromes. Issue 3 (6th July 2022) - Al Ojaimi, Mode; Banimortada, Bashar J.; Othman, Amna; Riedhammer, Korbinian M.; Almannai, Mohammed; El‐Hattab, Ayman W.
Abstract: Epigenetic modifications of DNA and histone tails are essential for gene expression regulation. They play an essential role in neurodevelopment as nervous system development is a complex process requiring a dynamic pattern of gene expression. Histone methylation is one of the vital epigenetic regulators and mostly occurs on lysine residues of histones H3 and H4. Histone methylation is catalyzed by two sets of enzymes: histone lysine methyltransferases (KMTs) and histone lysine demethylases (KDMs). KMT2 enzymes form a distinct multi‐subunit complex known as COMPASS to enhance their catalytic activity and diversify their biologic functions. Several neurodevelopmental syndromes result from defects in histone methylation which can be caused by deficiencies in histone methyltransferases and demethylases, loss of the histone methyltransferase activator TASP1, or derangements in COMPASS formation. In this review article, the molecular mechanism of histone methylation is discussed followed by summarizing clinical syndromes caused by monogenic defects in histone methylation. Abstract : Different syndromes associated with deficiencies of histone methyltransferases and histone demethylases.